(untitled) (The International Journal for Scientific Research, 2026)
This research examines the impact of the invalidity of the main contract on the arbitration clause under Saudi Arbitration Law, through an analytical study of the Arbitration Law issued by Royal Decree No. (M/34) dated 24/5/1433H (2012). The study focuses on Article 21, which establishes the principle of separability of the arbitration clause, providing that the invalidity, rescission, or termination of the main contract does not invalidate the arbitration clause as long as the clause is valid in itself. The study also addresses Article 20, which adopts the principle of competence-competence and grants arbitral tribunals the authority to rule on objections relating to their jurisdiction and the validity of the arbitration agreement. The research adopts analytical, comparative, and applied methodologies by examining relevant statutory provisions, reviewing recent decisions of Saudi Commercial Courts of Appeal, and comparing the Saudi approach with the UNCITRAL Model Law and selected comparative legal systems. The study concludes that the invalidity of the underlying contract does not affect the arbitration clause unless the defect directly affects the arbitration agreement itself, such as lack of writing, incapacity, or defective consent. It also finds that Saudi courts strongly support the separability principle and limit judicial review to the exclusive grounds for annulment. The study recommends wider publication of judicial principles, careful drafting of arbitration clauses, and increased specialized training for arbitrators, judges, and lawyers to enhance confidence in commercial arbitration and strengthen the investment environment in the Kingdom of Saudi Arabia.